Seeds for traditional crops - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Zambian nutritional experts are echoing findings by local agricultural scientists, in order to encourage consumers to grow and buy time-tested traditional food varieties. Zam Seed, the national seed company funded by the Swedish International...